1992
DOI: 10.1002/jctb.280550206
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic kinetics of nickel/calcium aluminate catalyst for methane steam reforming

Abstract: A new catalyst for steam reforming of methane based on nickel/calcium aluminate is prepared. The new catalyst has shown stability and high activity at low steam to methane ratios. In this paper the intrinsic rate equations are derived and parameters estimation made. The rate equations show non-monotonic dependence on steam partial pressure. The rate equations also show that the primary product is CO, while CO is formed via the reverse water-gas shift reaction. The mechanism proposed and the rate equations obta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(20 citation statements)
references
References 9 publications
0
19
0
1
Order By: Relevance
“…Under conditions of thermodynamic equilibrium the question is irrelevant, however, far from equilibrium it grows in significance. Furthermore, the nature of the rate determining step (RDS) of the steam reforming and the role of the support [19,20] are key parameters to understand the reaction in further detail and facilitate comparison between different investigations. The classical SR catalyst is a metal (nickel) on a (usually basic) support, which is assumed to be inert [13] or affect the reaction [21].…”
Section: Introductionmentioning
confidence: 99%
“…Under conditions of thermodynamic equilibrium the question is irrelevant, however, far from equilibrium it grows in significance. Furthermore, the nature of the rate determining step (RDS) of the steam reforming and the role of the support [19,20] are key parameters to understand the reaction in further detail and facilitate comparison between different investigations. The classical SR catalyst is a metal (nickel) on a (usually basic) support, which is assumed to be inert [13] or affect the reaction [21].…”
Section: Introductionmentioning
confidence: 99%
“…The models comprise a kinetic force, a driving force and an adsorption term, albeit sometimes in a modified form . Some highly cited examples are the models proposed by Bodrov et al, Khomenko et al, Xu and Froment, Soliman et al, and Hou and Hughes, see Supporting Information Table S2. In these models, it is typically assumed that, to a certain extent, hydrogen can inhibit the reaction rate .…”
Section: Methodsmentioning
confidence: 99%
“…The assessment of the Numaguchi model and the experimental data suggested that including competitive adsorption effects may be helpful to improve the model performance. Reactant adsorption is, hence, incorporated in the next iteration of the methodology, see steps (5) to (8) in Table , which contain both gas phase and surface species. The adsorption and desorption of methane and water are assumed to be quasiequilibrated based on the fact that methane dissociation is the most demanding and, hence, rate‐determining step.…”
Section: Application Of the Systematic Methodology On Smrmentioning
confidence: 99%
“…A complex model developed by Avetisov et al [61] converges to the model devel oped by Xu and Froment [59] under usual operating conditions of SMR. Moreover, the same reaction path is successfully used to develop the kinetic rate expressions for supported nickel catalysts by many authors [62][63][64]. Model developed by Xu and Froment [59] is also used extensively for modeling of SMR process [65][66][67][68][69][70][71][72][73][74] and is used in this work also.…”
Section: On the Modeling Of Steam Methane Reformingmentioning
confidence: 99%